Síntese de hidróxido duplo lamelar: efeitos do processo de secagem - Silva Neto, Luiz Daniel da (Universidade Federal de São Carlos, 2020)
Because of its chemical versatility, ionic exchange and regeneration capacity, Layered Double Hydroxides (LDHs), have recently been recognized as a promising material due to their many application areas. Drying is an essential process in obtaining the desired properties for the nanomaterial, being an essential step for the formation of the morphological structure of these materials. This study aimed to evaluate the influence of the drying process on MgAl–CO3/LDH synthesis. LDH synthesis was performed according to the coprecipitation method described by Reichle, maintaining a ratio of 2:1 Mg/Al. A study on drying kinetics was carried out at temperatures of 75, 90 and 105°C. For the drying stage, experimental planning with 22 with 4 axial points and 3 repetitions at the point was assembled. The description of the structure of the materials produced was carried out through X-ray diffraction (XRD), thermogravimetric analysis (TG/DTG), Brunauer, Emmett and Teller (BET) technique and Fourier transform infrared spectroscopy (FTIR). For drying kinetics, a predominantly convective mass transport was observed with a reduction of the total drying time by approximately 35% with the addition of drying air. The empirical equations that presented the best adjustments were Page, Page Modified and Midilli et al. The LDHs obtained presented type IV isotherms and the presence of hysteresis from the presence of mesopores. The surface area and pore diameter ranged from 4.09 m2/g to 18.55 m2/g and 12.50 nm to 24.46 nm, respectively. The presence of micropores could not be observed. The FTIR analysis showed characteristic bands of chemical bonds in all parameters studied, presenting variation in band intensity. Thermogravimetric analysis is typical and proceeds successively by the loss of adsorbed, interlamellar water, carbon dioxide and dehydrogenation, presenting different values in the loss of mass for drying conditions. Through XRD analysis and the use of Scherrer, Williamson-Hall and Halder-Wagner methods, there was a tendency to increase crystallite size with the drying temperature increase from 13.10 nm to 38.94 nm. Besides, the variation in basal spacing was observed, ranging from 7,520 Å to 7,543 Å.
Synthesis of layered double hydroxides: effects of drying process
Keywords: Secagem; Espaçamento basal; Hidróxido duplo lamelar; Hidrotalcita; Drying; Basal spacing; Layered double hydroxides; Hydrotalcite; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA